If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.6-6=-0.40(e-10)-7
We move all terms to the left:
0.6-6-(-0.40(e-10)-7)=0
We add all the numbers together, and all the variables
-(-0.40(e-10)-7)-5.4=0
We calculate terms in parentheses: -(-0.40(e-10)-7), so:We get rid of parentheses
-0.40(e-10)-7
We multiply parentheses
-0.4e+4-7
We add all the numbers together, and all the variables
-0.4e-3
Back to the equation:
-(-0.4e-3)
0.4e+3-5.4=0
We add all the numbers together, and all the variables
0.4e-2.4=0
We move all terms containing e to the left, all other terms to the right
0.4e=2.4
e=2.4/0.4
e=5+0.4/0.4
| 3(x+6)2(3x-4)=-50 | | /0.3y+0.18=1.5y-0.42 | | 2x+9+7=x+12 | | 10q−q−3q+6q=–16 | | 3(x-4)-7=-3(-8x+1)-7x | | 9/5x+3/2x=-33/10 | | (3x-22)+x=180=80+x+x | | 10q−–q-–3q+–6q=–16 | | 3(x-4)-7=-3(-8+1)-7x | | -10x-5=95 | | 5x/4+5=15/2 | | 6(6y+5)-24=3(4y+1)+3 | | 62.10=20+.5x+.15(20+5x | | -7x-33=-2(x+9) | | 10h+2h+3h-9h+2h=16 | | 48=-6(1-6x)-(7x+4) | | 11c-2c=9 | | 11=-1.2q+16 | | F(1)=-3x+10 | | 4(2x+1)=3(4x-4) | | 11m^2=34m+40 | | x/6=x+4/4 | | -3(4v-1)+3v=3(v+3) | | 2x-3/10=0.5+3/5 | | 11+m/2=3 | | 2x+9/2=5 | | 9(v-1)=7v-23 | | x-46+x+90+90=360 | | 35g+11g-41g+12g=17 | | F(0)=-3x+10 | | 17b-6b-7b=44 | | 2(3x•+5)=-19+23 |